1976
DOI: 10.1901/jaba.1976.9-355
|View full text |Cite
|
Sign up to set email alerts
|

The Generalization Effects of Parent Training Across Stimulus Settings

Abstract: Five parents of nonverbal children were trained in two home settings to modify antecedents and consequences to their children's vocalizations. Generalization effects of the parent training on both the parent's and children's behaviors under different stimulus conditions were investigated using multiple-baseline designs. Increases in parent prompting and reinforcing their children's vocalizations generalized only minimally to a new setting in the home where parent training had not occurred. Child increases in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
1

Year Published

1977
1977
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 14 publications
0
22
1
Order By: Relevance
“…All parents may benefit from specific training to optimize their natural role as first language teachers; however, such training may be especially important when children are having difficulty learning language. Enhancing parents' effectiveness as language teachers for their young children with developmental delays has been a topic of systematic inquiry for more than 15 years (c.f., MacDonald, Blott, Gordon, Spiegel, & Hartman, 1974;Miller & Sloane, 1976). By enhancing parents' use of naturalistic strategies that have been shown to be effective in teaching children new language skills, it is presumed that children will learn specific communication skills, generalization from other language training will be enhanced, and ultimately, that their language development will be facilitated (Kaiser, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All parents may benefit from specific training to optimize their natural role as first language teachers; however, such training may be especially important when children are having difficulty learning language. Enhancing parents' effectiveness as language teachers for their young children with developmental delays has been a topic of systematic inquiry for more than 15 years (c.f., MacDonald, Blott, Gordon, Spiegel, & Hartman, 1974;Miller & Sloane, 1976). By enhancing parents' use of naturalistic strategies that have been shown to be effective in teaching children new language skills, it is presumed that children will learn specific communication skills, generalization from other language training will be enhanced, and ultimately, that their language development will be facilitated (Kaiser, 1993).…”
mentioning
confidence: 99%
“…Didactic studies commonly reported child acquisition of specific target skills during training sessions. There is limited evidence of generalization to spontaneous use in these studies (e.g., Miller & Sloane, 1976). Responsive Interaction studies have measured the impact of the parents' intervention on children's global language development (e.g., Tannock et a[., 1989) and, sometimes, other aspects of their development (e.g., Mahoney & Powell, 1988).…”
mentioning
confidence: 99%
“…This lack of consistent response by parents to training procedures has prompted researchers to identify marital, psychopathological, attitudinal, socioeconomic, and community contact variables that will discriminate families who are successful and unsuccessful in parent training (Griest & Wells, 1983;Wahler & Graves, 1983). Other research has shown that parents may have more difficulty in applying contingency management procedures in some settings than in others (Miller & Sloane, 1976;Sanders & Glynn, 1981). For example, some parents may require setting specific interventions to manage their children at mealtimes, bedtime, or on visits to the community such as shopping trips or dining out (Bauman, Reiss, Rogers, & Bailey, 1983;Sanders & Hunter, 1984).…”
mentioning
confidence: 99%
“…Evidence from the parent training field indicates that parents do not necessarily apply their skills to other untreated problem behaviors, other siblings, new settings, or when therapist contact terminates (e.g., Forehand & Atkeson, 1977;Miller & Sloane, 1976;O'Dell, Flynn & Benlolo, 1977;Patterson, 1974;Rosenthal, 1976).…”
mentioning
confidence: 99%